Österreichs Skisport im Nationalsozialismus: Anpassung - Verfolgung - Kollaboration - Praher, Andreas (2021)
The history of Nazi indoctrination in Austria's skiing does not begin in March 1938. Even before that, a turn to National Socialism can be traced. Andreas Praher investigates power structures and scope for action in skiing before and during the Nazi era as well as in post-war Austria.